(untitled) (Eurasian Scientific Herald, 2023)
Uzbekistan has been making significant strides towards modernizing its logistics sector in recent years. This has led to the emergence of various opportunities for foreign investors seeking to tap into the country’s growing economy. However, investment in the logistics sector of Uzbekistan is not without its challenges. This article examines the current state of the logistics sector in Uzbekistan and the challenges and opportunities that investors may encounter when considering investment in this sector. The article concludes by highlighting the strategies and best practices that investors can use to navigate these challenges and capitalize on the opportunities presented by the logistics sector of Uzbekistan.